When Comedy Meets Politics: Symbolic Capital and The Electoral Phenomenon of Komeng in Indonesia’s 2024 DPD Election - Muhammad Fadhil Abdur Rahim; Yusa Djuyandi; Ratnia Solihah (Journal of Social Work and Science Education, 2026)
This study analyzes how Alfiansyah Bustami Komeng utilized symbolic capital to secure 5,399,699 votes, the highest nationally in Indonesia’s 2024 Regional Representative Council (DPD) election from West Java. Employing a descriptive qualitative approach with a single instrumental case study grounded in Bourdieu’s theory of capital, the research draws on official KPU documents, national media coverage (January–April 2024), social media data, and academic literature. The findings identify two primary symbolic capital dimensions: (1) popularity/fame accumulated over 35 years in the entertainment industry, and (2) a positively perceived charismatic image reinforced by an anti-expensive-politics narrative and absence of scandal. The study reveals that the DPD’s non-partisan, personal-vote-based First-Past-The-Post system structurally advantages high-symbolic-capital candidates. Komeng’s atypical zero-cost campaign centered on a viral ballot photograph and official name change amplified his symbolic capital into substantial electoral appeal. This research extends Bourdieusian theory by demonstrating how symbolic capital functions as a legitimacy heuristic in Global South democracies characterized by information asymmetry. The findings carry implications for understanding celebrity politics, institutional design of non-partisan representation, and the quality of electoral democracy in Indonesia.